Introduction to instructed second language acquisition - Loewen, Shawn (New York : Routledge, 2015)
'Introduction to Instructed Second Language Acquisition is the first book to present a cohesive view of the different theoretical and pedagogical perspectives that comprise instructed second language acquisition (ISLA), defined as any type of learning that occurs as a result of the manipulating the process and conditions of second language acquisition. The book begins by considering the effectiveness of ISLA and the differences between ISLA and naturalistic L2 learning. It then goes on to discuss the theoretical, empirical, and pedagogical aspects of such key issues in ISLA as grammar learning; interaction in the classroom; focus on form, function and meaning; vocabulary learning; pronunciation learning; pragmatics learning; learning contexts; and individual differences. This timely and important volume is ideally suited for the graduate level ISLA course, and provides valuable insights for any SLA scholar interested in the processes involved in second language learning in classroom settings'--
Includes bibliographical references (pages 185-201) and index.
Keywords: Second language acquisition -- Study and teaching